Sosialisasi dan Pelatihan Sistem Informasi Manajemen Pemberdayaan Kesejahteraan Keluarga Terintegrasi Berbasis Kampung: Socialization and Training of Village-Based Integrated Family Welfare Empowerment Management Information Systems - Zaidir, Zaidir; Sujarweni, Veronika Wiratna; Erizal, Erizal; Diqi, Muhammad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Empowering family well-being in rural communities is a crucial goal in sustainable development. One emerging innovation is the Village-Based Integrated Family Welfare Information System (VBIFWIS). This study delves into the effectiveness of the socialization and training of VBIFWIS in addressing the challenges of family empowerment in rural areas. The findings indicate that adequate socialization and targeted training can enhance the community's understanding of the benefits of VBIFWIS, improve access to services, and empower individuals in system utilization. However, initial challenges such as technology resistance and the learning curve necessitate a sustained approach. These findings provide valuable insights into how VBIFWIS can effectively empower family well-being in rural environments, emphasizing the significance of community participation, efficient data management, and addressing technological challenges.